Bound electronic states of the smallest fullerene C20− anion - Yang, Yifan; Klaiman, Shachar; Gromov, Evgeniy; Cederbaum, Lorenz S. (Physical chemistry, chemical physics, 2018)
We report on high-level coupled-cluster calculations for the anion states of the smallest fullerene C20. Using the state-of-the-art EA-EOM-CCSD method we revealed that the C20− anion has five bound electronic states at the C20 neutral ground-state D3d equilibrium configuration. These are two pairs of 2Eu and 2A2u states and one 2A1g state. The binding energies vary from 2.05 eV for the most bound 2Eu state to <1 meV for the 2A1g state. An analysis in terms of radial and angular density distribution of the excess electron revealed that the two 2Eu/2A2u pairs are valence-like states while 2A1g corresponds to a super-atomic-like (SAMO) state. The valence states of the first 2Eu/2A2u pair were found to be of p-type whereas those of the second pair are of hybrid sp-type. We have also applied a simple model to understand the binding of the excess electron in C20−. The model confirms the existence of only one SAMO state of the s-type for C20−. At the same time, it overestimates the number of the bound valence states of C20−.
Im Titel erscheint die Zahl 20 tiefgestellt und das Minus-Zeichen hochgestellt
Gesehen am 22.04.2020